2013
DOI: 10.1038/sj.bdj.2013.627
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, diabetes and periodontitis – a triangular relationship?

Abstract: The global rise of obesity, both adult and childhood, has been paralleled by a rise in type 2 diabetes, a trend predicted to continue for at least the next two decades. The combined effect will create a burden of direct and co-morbidities that will strain the physical and financial resources of all countries. While it is accepted that both type 1 and type 2 diabetes are major risk factors for the development and progression of periodontal disease, there is growing evidence that obesity is both an indirect risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 61 publications
0
50
0
5
Order By: Relevance
“…Moreover, it has been proposed that periodontitis prompts an inflammatory alteration in adipose tissue, which is associated with obesity, DM, and periodontal sickness (4).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been proposed that periodontitis prompts an inflammatory alteration in adipose tissue, which is associated with obesity, DM, and periodontal sickness (4).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity is rising worryingly not only among adult but also among children in many developed and developing countries [1]. It is defined as excessive fat accumulation that can cause various health disorders [2].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive adiposity can promote chronic low grade inflammation [15,16]. Obesity and its related health problems become a burden on the economy of many countries, requiring action across individual and societal levels [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the periodontal tissues mount an immune inflammatory response to bacteria and their products, systemic challenges with these agents also induce a major vascular response offering explanatory mechanisms for the interaction between periodontal infections and a variety of systemic disorders [17,18]. Epidemiological studies have suggested that periodontal deterioration increases the risk of systemic problems such as chronic obstructive pulmonary diseases (COPDs), stroke [19], cardiovascular diseases (CVDs) [20], atherosclerosis, diabetes mellitus (DM) [21], adverse pregnancy outcomes [22]. Periodontal diseases have proved to be an independent risk factor for adverse pregnancy disorders such as preterm births, low birth weight and pre-eclampsia, after adjusting for other confounding factors [23].…”
Section: Introductionmentioning
confidence: 99%